(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Myocardial infarction often referred to as a heart attack, is an acute condition that results from a blockage in a coronary artery. This causes damage to the heart muscle due to lack of oxygen. The causes of myocardial infarction are varied, but the most common risk factors are smoking, high blood pressure, high cholesterol, and diabetes.